2022
DOI: 10.1002/clc.23809
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the “atherosclerotic pabulum” on in‐hospital mortality for SARS‐CoV‐2 infection. Is calcium score able to identify at‐risk patients?

Abstract: Background Although the primary cause of death in COVID‐19 infection is respiratory failure, there is evidence that cardiac manifestations may contribute to overall mortality and can even be the primary cause of death. More importantly, it is recognized that COVID‐19 is associated with a high incidence of thrombotic complications. Hypothesis Evaluate if the coronary artery calcium (CAC) score was useful to predict in‐hospital (in‐H) mortality in patients with COVID‐19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“… 28 did not find age to be an independent predictor of death in COVID-19 patients. In contrast, many studies have recognized age as an independent predictor of death in COVID-19 patients 32 , 34 , 35 , 42 , 43 . This disparity can be attributed to differences in study populations, as our patients had a lower mean age compared to previous studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“… 28 did not find age to be an independent predictor of death in COVID-19 patients. In contrast, many studies have recognized age as an independent predictor of death in COVID-19 patients 32 , 34 , 35 , 42 , 43 . This disparity can be attributed to differences in study populations, as our patients had a lower mean age compared to previous studies.…”
Section: Discussionmentioning
confidence: 90%
“… 33 reported that ICU admission and longer ICU stay were associated with higher odds of mortality in COVID-19 patients with CAC scores above the median. However, some studies have not reported a significant association between CAC score and ICU admission or length of ICU stay 32 , 34 , 35 . This variability in findings could be attributed to differences in patient categorization based on CAC score, sample size, or CAC scoring method.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, in the context of sepsis, reflex tachycardia increases the myocardial oxygen demand. Of course, the presence of atheroma plaques is a risk factor for the unfavorable evolution in patients with sepsis, increasing the risk of acute myocardial injury [ 61 , 62 ], but COVID-19 is also highly associated with non-atherosclerotic coronary perfusion impairment, such as spasm of the coronary arteries, dissection of the coronary wall, microthrombosis in the context of the hypercoagulant state, or vasculitis-like injury of the coronary vessels [ 63 , 64 ]. Regardless of the intimate mechanism of COVID-19-related myocardial infarction with non-obstructive coronary arteries, the patients’ prognosis is poor, with high mortality rates mainly due to the increased prevalence of severe comorbidities, such as ARDS, obesity, or congenital thrombophilia [ 64 , 65 ].…”
Section: Cardiovascular Pathophysiology Related To Covid-19 and The M...mentioning
confidence: 99%
“…Moreover, there are no specifications about the type of coexisting comorbidities since the severity of COVID-19 pneumonia could have been related to many pathologies, above all cardiovascular disease. 4 In our opinion, images should have been reviewed by at least two expert radiologists for more reliable detection of radiological signs in HRCTs. This method should have been reported in the study's limitations.…”
mentioning
confidence: 99%